2006
DOI: 10.1677/erc.1.00938
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials with retinoids for breast cancer chemoprevention

Abstract: Retinoids have been studied as chemopreventive agents in clinical trials due to their established role in regulating cell growth, differentiation and apoptosis in preclinical models. Experimental evidence suggests that retinoids affect gene expression both directly, by activating and/or repressing specific genes, and indirectly, by interfering with different signal transduction pathways. Induction of apoptosis is a unique feature of fenretinide, the most widely studied retinoid in clinical trials on breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 94 publications
0
73
0
3
Order By: Relevance
“…Fenretinide has been widely used in clinical trials for breast cancer chemoprevention ( 5 ) and for treatment of neuroblastoma and Ewing sarcoma ( 6 ). It has been shown that fenretinide inhibits the proliferation of many tumor cell lines (7)(8)(9)(10)(11), whereas it manifests minimal cytotoxicity to nonmalignant cells ( 7,12 ).…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…Fenretinide has been widely used in clinical trials for breast cancer chemoprevention ( 5 ) and for treatment of neuroblastoma and Ewing sarcoma ( 6 ). It has been shown that fenretinide inhibits the proliferation of many tumor cell lines (7)(8)(9)(10)(11), whereas it manifests minimal cytotoxicity to nonmalignant cells ( 7,12 ).…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…[9][10][11][12][13] We, along with others, also have found that ATRA induces osteoblastic differentiation of osteosarcoma cells both in vivo and in vitro. 14,15 Moreover, ATRA has been found to induce osteoblastic differentiation of mouse and rat mesenchymal stem cells and preosteoblasts.…”
Section: Introductionmentioning
confidence: 98%
“…Fenretinide is a retinamide with both chemopreventative (Zanardi et al, 2006) and chemotherapeutic properties in a range of adult malignancies (Chiesa et al, 2005;Simeone et al, 2005), and has manageable toxicity in adults (Formelli et al, 1993;Pienta et al, 1997) and children (Garaventa et al, 2003;Villablanca et al, 2006). We have reported previously that fenretinide induces cell death in the Ewing's sarcoma family of tumours (ESFT) in vitro and reduces ESFT growth in vivo (Myatt et al, 2005), suggesting it may represent a novel therapeutic strategy for the treatment of this aggressive tumour of bone and soft tissue (Burchill, 2003).…”
Section: Introductionmentioning
confidence: 99%